The Symbol of Caring for the Environment on a Poster Image by Grade 6 Students at SDIT Nurul Yaqin Jakarta - Jatut Yoga Prameswari; Yulianto Hadiprawiro; Dewi Indah Susanti (Universitas Indraprasta PGRI, 2022)
Poster as a medium of informative artwork to convey information to the public. In educational institution, poster as a medium is used for delivering messages, due to the spesific subject or thematic topics. In this paper, poster was designed by elementary student as assignments in the subject of Arts, Culture and Crafts (SBdP) in schools. This study aims to describe the symbols and meanings of posters created by students. This research method used descriptive qualitative research method with research instrument using Pierce. The results of the study show that indexically, apart from appreciating students work, the function of the poster is actually used by the school or teacher, especially as a campaign media in schools that can be directly seen by school residents. Where in the poster also has a persuasive function, connotative and denotative meanings that invite the audience to take part in protecting and saving the environment.Keywords: Semiotic, persuasive, poster, environment, student’s drawing.